126 Urinary Incontinence: Prevalence, Clinical Characteristics and Impact on Quality of Life of Older People in Ireland. (16th September 2019) - Claffey, Paul; Sullivan, Rachel; Anne Kenny, Rose; McNicholas, Triona; Briggs, Robert
Abstract: Background: Urinary incontinence (UI) is one of the 'giants' of gerontological care, associated with early mortality, depression and falls in later life. It is often amenable to treatment, yet clinical experience suggests that older people with urinary incontinence often go undiagnosed and therefore untreated. The aim of this study therefore was to ascertain the prevalence of UI in a large population representative sample of Irish adults ≥50 years; to examine how often participants report UI to healthcare professionals; to profile factors associated with UI and its impact on quality of life (QOL). Methods: This study was embedded within the Irish Longitudinal Study on Ageing. Participants were a population-representative sample of almost 7, 000 Irish adults aged ≥50 years. UI was defined as any involuntary loss of urine from the bladder within the last 12 months, based on the International Continence Society Definition. QOL was measured using the Control, Autonomy, Self-realisation and Pleasure-19 Scale (CASP-19). Results: Fifteen % (1, 061/6, 996) of participants had UI within the last 12 months; 9% (269/3, 162) of males and 21% (792/3, 834) of females. Almost half (486/1, 061) of participants with UI had not reported it to a healthcare professional, with one fifth (240/1, 061) reporting UI limited everyday activities. Logistic regression modelling demonstrated UI was associated with advancing age, female sex, alcohol excess, polypharmacy, chronic disease and depression. Linear regression models showed that UI was associated with significantly lower self-rated QOL, as measured by CASP-19 (β =-1.13 (95% CI: -1.69 - -0.57), p <0.001). Conclusion: UI affects 1 in 7 people aged ≥50 years. It is closely associated with other geriatric syndromes such as polypharmacy, depression and multimorbidity and impacts significantly on QOL. Despite this, almost half of those with UI do not report symptoms to a healthcare professional, highlighting the need for structured assessment of UI as part of comprehensive age-attuned care.